2015
DOI: 10.1039/c5ra00858a
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of sewage sludge derived carbonaceous catalyst for m-cresol catalytic wet peroxide oxidation and degradation mechanism

Abstract: Sewage sludge derived carbonaceous materials (SWs) treated with different kinds of acid were used as the catalysts for catalytic wet peroxide oxidation (CWPO) of m-cresol in batch reactor and continuous reactor, respectively. The results showed that SW treated with nitric acid (HNO 3 -SW) and sulfuric acid (H 2 SO 4 -SW) exhibited high catalytic activity in a CWPO reaction. The conversion of m-cresol reached 100%, after CWPO reaction for 3 h at an initial pH of 7 and a temperature of 25 C over a H 2 SO 4 -SW c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…As shown in Figure 8, high conversions and removal rates of phenol were maintained at pH 7 and pH = 10. Then we found out that the pH value of phenol solutions were decreased from 7.0 to 4.0 and 10.0 to 7.1 after the PS was added, which is consistent with the previous study [42]. Therefore, the reactions were under the pH of 4.0 and 7.1.…”
Section: Effect Of Initial Phsupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure 8, high conversions and removal rates of phenol were maintained at pH 7 and pH = 10. Then we found out that the pH value of phenol solutions were decreased from 7.0 to 4.0 and 10.0 to 7.1 after the PS was added, which is consistent with the previous study [42]. Therefore, the reactions were under the pH of 4.0 and 7.1.…”
Section: Effect Of Initial Phsupporting
confidence: 90%
“…Res. Public Health 2020, 17, x 9 of 15 after the PS was added, which is consistent with the previous study [42]. Therefore, the reactions were under the pH of 4.0 and 7.1.…”
Section: Effect Of Initial Phsupporting
confidence: 88%
“…Pyrolysis is a conventional process to heat predried sewage sludge at temperatures of 350–800 °C in an anaerobic atmosphere . Besides being used as sorbents to remove harmful gases (e.g., SO 2 and H 2 S) or organic pollutants (e.g., dyes and chlorinated organics), , pyrolyzed sewage sludge was also explored for some new applications. , For instance, Dai’s group synthesized a sewage sludge-derived Fe-loading nanocomposite via a one-step pyrolysis method, and employed it as a stable heterogeneous photo-Fenton catalyst to remove rhodamine B and p -nitrophenol . Yuan et al prepared a composite TiO 2 photocatalyst with using sewage sludge as the support and the dopant source and found the resulting composite photocatalyst could remove p -nitrophenol more efficiently than TiO 2 P25 under visible light .…”
Section: Introductionmentioning
confidence: 99%
“…Sewage sludge-derived AC-based catalysts have also been used during the catalytic wet peroxide oxidation (CWPO) of m-cresol (initial substrate = 100 mg/L). 33,34 The available large number of studies using AC-and Al 2 O 3 -supported catalysts investigated CWO performance with a single substrate (i.e., phenol). Moreover, it was observed that the majority of the studies used a low phenol concentration (=0.5−5.0 g/L) except few studies in which phenol concentration was varied from 1 to 10 g/L.…”
Section: Introductionmentioning
confidence: 99%
“…However, no information about carbon removal was provided. Sewage sludge-derived AC-based catalysts have also been used during the catalytic wet peroxide oxidation (CWPO) of m -cresol (initial substrate = 100 mg/L). , …”
Section: Introductionmentioning
confidence: 99%